Si fa ma non si dice. Esiti di un’indagine quantitativa sulla terza missione degli antropologi accademici italiani - Basile, Dario (Antropologia Pubblica, 2024)
This research report presents the findings of a quantitative investigation of Italian anthropologists’ research and third mission activities, based on questionnaires mailed to all Italian Anthropology professors (Scientific-Disciplinary Sector M-DEA/01) in May/June 2020. The results of this survey were compared to those of another national study of academics’ third mission activities carried out in 2015/2016. This survey’s goal is to discover how much Italian anthropologists were committed over the 2015-2020 period to some activities, aimed at engaging universities in the public sphere. In fact, the results of this study point to a high level of participation in Academic Engagement and, even more, in Public Engagement. These activities have mainly a local dimension, a sort of Community Engagement. Moreover, it was unexpected to find out that there is a statistical positive correlation between Public and Academic Engagement activities and research activities. We discover that Italian anthropologists are not less engaged with institutions and companies than their colleagues of other disciplines. But unexpectedly Italian anthropologists’ high level of third mission has apparently not paid off in terms of academic recruitment, as shown by a comparison with such neighboring disciplines as Sociology and Psychology in the last 10 years.